Computational Studies of Cardiac and Skeletal Troponin - Bowman, Jacob D.; Lindert, Steffen (Frontiers in Molecular Biosciences, 2019)
Troponin is a key regulatory protein in muscle contraction, consisting of three subunits troponin C (TnC), troponin I (TnI), and troponin T (TnT). Calcium association to TnC initiates contraction by causing a series of dynamic and conformational changes that allow the switch peptide of TnI to bind and subsequently cross bridges to form between the thin and thick filament of the sarcomere. Owing to its pivotal role in contraction regulation, troponin has been the focus of numerous computational studies over the last decade. These studies elegantly supplemented a large volume of experimental work and focused on the structure, dynamics and function of the whole troponin complex, individual subunits and even on segments of the thin filament. Molecular dynamics, Brownian dynamics and free energy simulations have been used to elucidate the conformational dynamics and underlying free energy landscape of troponin, calcium and switch peptide binding, as well as the effect of disease mutations, small molecules and post-translational modifications such as phosphorylation. Frequently, simulations have been used to confirm or explain experimental observations. Computer-aided drug discovery tools have been employed to identify novel potential calcium sensitizing agents binding to the TnC-TnI interface. Finally, Markov modeling has contributed to simulating contraction within the sarcomere on the mesoscale. Here we are reviewing and classifying the existing computational work on troponin and its subunits, outline current gaps in simulations elucidating troponin’s role in contraction and suggest potential future developments in the field.